Constraints perceived by dairy farmers of Kerala State - vishnumoorthy, sreeram (Indian Journal of Dairy Science, 2017)
Dairying is a major subsidiary occupation for the farmers of Kerala. But the present day dairying is faced with a number of challenges. The study was conducted in four districts of the State, selected purposively, to explore various constraints associated with dairy farming as perceived by the farmers following the Rank Based Quotient (RBQ) method. Results showed that increased price of cattle feed, non remunerative price of milk, high cost of credit, unavailability of required manpower for cattle health care, unavailability of dry and green fodder etc. were some of the important constraints reported by majority of the farmer respondents. Interventions including financial support to contain the cattle feed price along with periodic revision of milk price on rational grounds, due recognition of the sector at par with the crop husbandry etc. are suggested. Also the present study brings the need for well planned actions for better coordination among the line departments, building more networks and partnerships with other relevant service providers and strengthening of the dairy extension and advisory services under long term strategic interventions.Â